Gambaran Tingkat Kecemasan Warga di Daerah Rawan Bencana Banjir Desa Laban Kabupaten Sukoharjo - Annisa Shinta Devi; Hermawati Hermawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Disasters are one of the main problems that often occur in Indonesia, many impacts are caused by disasters. One of them is flooding, which is the result of a disaster. According to data from the Regional Disaster Management Agency (BPBD) in 2023, flooding occurred in Sukoharjo Regency, Mojolaban District, one of the sub-districts where flooding often occurs. Flooding has a psychological impact in the form of anxiety disorders. Anxiety is a normal reaction to situations that make a person's life very difficult. The aim of the research is to determine the level of anxiety of residents in flood-prone areas in Laban Village, Sukoharjo Regency. The research method used is quantitative descriptive. Sampling used purposive sampling technique with a total sample of 76 respondents. Data analysis uses univariate analysis. The research results showed that 48 people had mild anxiety or 80%, 7 people had moderate anxiety or 11.7%, 5 people had no anxiety or 8.3%, and no one experienced severe or very severe anxiety. The majority of residents in areas prone to flood disasters, Laban Village, Sukoharjo Regency, experienced mild anxiety, with 53 people experiencing mild anxiety.